(untitled) (Journal of actual problems of jurisprudence, 2018)
Legislation in the field of waste management has recently undergone major changes and additions. Kazakhstan concluded a number of agreements and conventions, the implementation of which is ensured by national legislation. The article analyzes the structure and content of the system of national legislation in the field of waste management. The constitutional and legal foundations of this legislation are determined. The complexity of this institution, provided by administrative, environmental, tax and other legislation, is analyzed. The analysis of the acts is made on the basis of a hierarchical analysis of normative legal documents. This allowed us to trace the existence of a unified system of normative acts, which provides comprehensive coverage of the necessary legal relations. Key words: production waste, consumption waste, system of legislation, environmental legislation